Pengaruh Model Core dengan Pendekatan Open Ended terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP - Putri Safrina Wahyuningtyas; Yani Setiani; Etika Khaerunnisa (Urogram Studi Pendidikan Matematika, Universitas IVET, 2020)
This research is motivated by the low ability of problem solving skills of junior high school students. So that a learning model needed that can enhance this ability. The CORE model with open ended approach is believed to be able to improve problem solving skills in junior high school students. The research was conducted in Junior High School 8 Serang 2018/2019 academic year which aim to see the influence of CORE model with open ended approach on problem solving skills of junior high school students. The research method used in this study is quasi-experimental with the type of design that is the nonequivalent pretest posttest control group design. This studi involved two classes consisting of the experimental class and the control class. The population in this study were all students of class grade VII of Junior High School 8 Serang. The sample of this tudy was the VII A class as experimental class and VII B class as control class. The instrumen used in this study was a mathematical problem solving test instrument. The result of the study provide the conclution that there is an influence of CORE model with open ended approach on problem solving.